2004
DOI: 10.1111/j.1537-2995.2004.03214.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased platelet aggregation of platelet concentrate during storage recovers in the body after transfusion

Abstract: These results suggest that the observed decreased in PLT aggregation after storage can improve in the body after transfusion, and transfused PLTs have similar aggregation ability compared to the PLTs derived from the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…Despite impaired aggregation in vitro, transfusion of PLTs with metabolic derangements accrued over 5 days of storage has resulted in recovery of PLT function in vivo 18,19 . Similarly, decreases in pH below 6.2 were not associated with any deficit of in vivo PLT recovery or survival 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Despite impaired aggregation in vitro, transfusion of PLTs with metabolic derangements accrued over 5 days of storage has resulted in recovery of PLT function in vivo 18,19 . Similarly, decreases in pH below 6.2 were not associated with any deficit of in vivo PLT recovery or survival 20 .…”
Section: Discussionmentioning
confidence: 98%
“…A number of reports have shown that in vitro function assays are reversed after transfusion of PLT stored in 100% plasma to recipients. Noteworthy, it has been shown that the aggregation response was restored after transfusion to thrombocytopenic patients 37,38 . Owens and colleagues 39 determined that 5‐day autologous, stored PLTs “quickly recovered adhesion and aggregability capabilities” upon transfusion to normal, healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,22 Resuspending PLTs stored in 100 percent plasma by autologous plasma stored separately may improve aggregation response, 22,38,55,73 indicating that reduced PLT aggregation during storage may improve in vivo after transfusion. 74 In PCs with low plasma content, however, PLT aggregation responses are severely diminished and only partly recover in the presence of full plasma or blood. 73 In our study we chose not to introduce additional influence on aggregation results by mechanical stress to PLTs in centrifugation, washing, and resuspending in plasma.…”
Section: Apelseth Et Almentioning
confidence: 98%